Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Memecahkan Masalah Geografi pada Siswa SMA - Klotilda Margareta Woa; Sugeng Utaya; Singgih Susilo (Graduate School of Universitas Negeri Malang, 2018)
This research was conducted at SMAN 1 Bajawa with the aim to know the effect of Problem Based Learning model of learning to solve the problem of geography in high school students. This type of research is quasi experiment with pretest and posttest control group design. The results of this study indicate that the average value of the ability to solve the problem of experimental class geography using Problem Based Learning model is higher and increased compared to the control class using the conventional learning model. This is proven also through hypothesis testing with independent samples test the ability to solve the problem of geography obtained results 0.030 <0.05 then the model of learning Problem Based Learning has a significant effect on the ability to solve the problem of geography of high school students. Based on the results of hypothesis testing can be concluded that the model of Problem Based Learning effective learning is used to improve the ability to solve the problem of geography of high school students. For Geography educator, it is suggested to use Problem Based Learning model to improve students' geography problem solving ability.Penelitian ini dilakukan di SMAN 1 Bajawa dengan tujuan untuk mengetahui pengaruh model pembelajaran Problem Based Learning terhadap kemampuan memecahkan masalah geografi pada siswa SMA. Jenis penelitian ini eksperimen semu (quasi experimen) dengan desain pretest and posttest control group. Hasil penelitian ini menunjukkan bahwa nilai rata-rata kemampuan memecahkan masalah geografi kelas eksperimen yang menggunakan model pembelajaran Problem Based Learning lebih tinggi dan mengalami peningkatan dibandingkan dengan kelas kontrol yang menggunakan model pembelajaran yang konvensional. Hal ini dibuktikan juga melalui uji hipotesis dengan independent samples tes kemampuan memecahkan masalah geografi diperoleh hasil 0,030 < 0,05 maka model pembelajaran Problem Based Learning berpengaruh signifikan terhadap kemampuan memecahkan masalah geografi siswa SMA. Berdasarkan hasil uji hipotesis tersebut dapat disimpulkan bahwa model pembelajaran Problem Based Learning efektif digunakan untuk meningkatkan kemampuan memecahakan masalah geografi siswa SMA. Bagi tenaga pendidik Geografi disarankan untuk menggunakan model pembelajaran Problem Based Learning untuk meningkatkan kemampuan memecahkan masalah geografi pada siswa.